Zakah Fund Distribution Model Trough Takaful Institution for The Welfare of The Poor Farmer - Intan Puspitasari; Neneng Ela Fauziyyah; Annisa Nur Salam (Global Review of Islamic Economics and Business, 2016)
Various poverty alleviation programs are always launched by the government from year to year. But it is not able to change the state of this country to become more self-sufficient and prosperous. If explored further, the majority of people classified as poor are working as farmers. Therefore, it is necessary to alleviate poverty policy that focuses on the welfare of farmers. So that when the policy is successfully realized, the majority of the poor in Indonesia will be able to independently through the development of the agricultural sector. One of the problems faced by farmers is weak stimulus funds from financial institutions. Due to the agriculture sector is seen as high risk, the financial institutions tend to feel worried if that financing for the sector. In anticipation of losses on crop failure, it is important applied an insurance that serves to protect the farm. So that financial institutions have the courage to do the financing for the agricultural sector. Meanwhile, zakat is one of the Islamic public financial instruments with the potential to be developed. Zakat funds channeled to 8 asnaf, including for the poor. So, it is possible if the charity can be used as agricultural insurance fund for farmers who are poor. Based on the explanation, this paper is intended to offer a model of the distribution of zakat to the poor farmers through takaful. The hope when this model is applied, will invite many financial institutions in stimulating agricultural business funds. The final implications are the farmers’ productivity increased and the quantity of the poor in Indonesia will be reduced.